2004
DOI: 10.1074/jbc.m401792200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Nuclear Factor 3 and Nuclear Factor 1 Regulate 5-Aminolevulinate Synthase Gene Expression and Are Involved in Insulin Repression

Abstract: Although the negative regulation of gene expression by insulin has been widely studied, the transcription factors responsible for the insulin effect are still unknown. The purpose of this work was to explore the molecular mechanisms involved in the insulin repression of the 5-aminolevulinate synthase (ALAS) gene. Deletion analysis of the 5 -regulatory region allowed us to identify an insulin-responsive region located at ؊459 to ؊354 bp. This fragment contains a highly homologous insulin-responsive (IRE) sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…125 An insulinresponsive region was identified at −459 bp to −354 bp, and this region was found to be required for insulin-mediated inhibition of the ALAS1 promoter. 126 The ALAS1 promoter also revealed motifs resembling consensus sequences for the binding of two nuclear proteins, hepatocyte nuclear factor 3β (HNF3β) and NF-1, involved in insulin repression of phosphoenolpyruvate carboxykinase (PEPCK) 127 and glucose transporter type 4 128 promoters, respectively. Insulin was not able to repress ALAS1 expression in HNF3-deficient HeLa cells, and HNF3β was shown to be involved in the basal expression of ALAS1.…”
Section: B Erythroid-specific Alas Genementioning
confidence: 99%
See 1 more Smart Citation
“…125 An insulinresponsive region was identified at −459 bp to −354 bp, and this region was found to be required for insulin-mediated inhibition of the ALAS1 promoter. 126 The ALAS1 promoter also revealed motifs resembling consensus sequences for the binding of two nuclear proteins, hepatocyte nuclear factor 3β (HNF3β) and NF-1, involved in insulin repression of phosphoenolpyruvate carboxykinase (PEPCK) 127 and glucose transporter type 4 128 promoters, respectively. Insulin was not able to repress ALAS1 expression in HNF3-deficient HeLa cells, and HNF3β was shown to be involved in the basal expression of ALAS1.…”
Section: B Erythroid-specific Alas Genementioning
confidence: 99%
“…Insulin was not able to repress ALAS1 expression in HNF3-deficient HeLa cells, and HNF3β was shown to be involved in the basal expression of ALAS1. 126 Furthering the implications of energy metabolism on ALAS1 expression, in 2005, Handschin et al 129 indicated that ALAS1 expression is regulated by the transcriptional coactivator peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1α). PGC-1α was originally identified in brown fat tissue and was shown to be a cofactor that interacts with the nuclear receptor family member peroxisome proliferator-activated receptor γ (PPARγ).…”
Section: B Erythroid-specific Alas Genementioning
confidence: 99%
“…The following elements were identified in the PGC1␣ promoter based upon TRANSFACT and PATCH: specificity protein 1 element (GGCTGGG), cyclic AMPresponse element (GACGTCA), hepatocyte nuclear factor 3 element(TGTGTGC), inverted CCAAT element (ICE)/nuclear factor Y element (ATTGG), and E1 box (CATGTG). We also noted additional conserved sequences that have been identified (35) …”
Section: Promoter Analysesmentioning
confidence: 99%
“…Cells-Because NFI has been reported to mediate the repression of several genes by insulin (15,16), quantitative real-time PCR was employed to determine the affects of insulin on TSH␤ expression in thyrotroph cells via NFI. T␣T1 cells were cultured in the indicated concentrations of insulin, and the mRNA expression levels of the ␣GSU and TSH␤ were determined.…”
Section: Nfi-b Is Involved In the Repression Of Tsh␤ By Insulin In Thmentioning
confidence: 99%
“…Insulin stimulates glucose uptake by many cells via a complex cascade of signaling events, and it affects GLUT4 gene transcription via NFI in adipose cells (13)(14)(15). Furthermore, NFI has been shown to mediate the repression of the 5-aminolevulinate synthase gene by insulin (16). However, no evidence has been presented regarding the direct influence of insulin on the binding of NFI protein to target gene promoters.…”
mentioning
confidence: 99%